Enhanced yield-mobility products in hybrid halide Ruddlesden–Popper compounds with aromatic ammonium spacers. Issue 37 (5th September 2019) - Venkatesan, Naveen R.; Mahdi, Ali; Barraza, Brian; Wu, Guang; Chabinyc, Michael L.; Seshadri, Ram
Abstract : Two hybrid halide Ruddlesden–Popper compounds using the cation 2-(4-biphenyl)ethylammonium show higher yield-carrier mobility products by time-resolved microwave conductivity than compounds with n -butylammonium cations. Abstract : Hybrid halide Ruddlesden–Popper compounds are related to three-dimensional hybrid AMX3 perovskites ( e.g. where A is a monovalent cation, M is a divalent metal cation, and X is a halogen) with the general formula L2 A n –1 M n X3 n +1 where L is a monovalent spacer cation. The crystal structure comprises perovskite-like layers separated by organic cation spacers. Here two Ruddlesden–Popper compounds with a conjugated cation, 2-(4-biphenyl)ethylammonium (BPEA) prepared by solvothermal and solvent evaporation techniques are reported. The structures of the two compounds: (BPEA)2 PbI4 and (BPEA)2 (CH3 NH3 )Pb2 I7, were solved by X-ray crystallography. The aromatic rings of the BPEA groups are well-separated in the organic layers leading to optical properties comparable to n = 1 and 2 hybrid halide Ruddlesden–Popper compounds with simpler alkyl ammonium cations. The ambient stability of both compounds over time was also confirmed by powder X-ray diffraction. Finally, the transient photoconductance, measured by time-resolved microwave conductivity, show that the compounds have maximum yield-mobility products respectively of 0.07 cm 2 V −1 s −1 and 1.11 cm 2 V −1 s −1 for (BPEA)2 PbI4 and (BPEA)2 (CH3 NH3 )Pb2 I7, both slightly enhanced over what has been measured for compounds with n -butylammonium spacer cations.